Model for developing trust on US construction projects. Issue 1 (5th February 2018) - Issa, Raja R.A.; Olbina, Svetlana; Zuppa, Dino
Abstract : Purpose: The purpose of this paper is to identify the factors found on US construction projects that are perceived by contractors to strengthen or weaken trust between contracting stakeholders and to develop a framework for evaluating these relationships. Design/methodology/approach: A comprehensive framework containing a number of factors (54) that could impact trust on construction projects was first developed. A survey questionnaire was then developed and administered via phone to contractors selected from the Engineering News Record top 400 US construction companies. The survey findings were then used to develop a trust model and case studies were used to validate and revise the trust model. Findings: A trust model is developed that helps large US contractors measure and improve trust with other stakeholders on their projects. Practical implications: Large US contractors are now provided with a tool not previously available to help them measure and improve trust between the different contracting parties on construction projects which can help them decrease project time and costs, and improve project results. Originality/value: The proposed trust model adds a number of different dimensions to the existing trust models found in the literature and as such improves the contractor's ability to foster and enhance trust on a US construction project.